PENGARUH PROFITABILITAS, LAPORAN KEBERLANJUTAN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN PERAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI PROFITABILITAS - Estianingtyas, Farah; Bayangkara, I. B. Ketut (LPPM Universitas Bina Bangsa, 2025)
This research study aims to analyzel the effect ofl profitability, sustainability reports, land company size on firml value by applying Goodl Corporate lGovernance (GCG) las a reinforcing or moderating variable in banking companiesl that have been listed on the Indonesia Stock Exchangel (IDX) during thel period l2019 - 2023. Based on the theory of management accounting, sustainability accounting, and Good Corporate Governance, the research utilizes quantitative data derived from the company's published financial statements and sustainability reports. The research method uses regression analysis in testing the hypothesis ofl the influence lof these variables on firm value, either partially or simultaneously. Findings from the resultsl of the study found that profitability, sustainability reports, company size have a positive influence on firm value, but the results are not significant where GCG acts as a moderating variable also does not moderate profitability on firm value, and profitability, sustainability reports, and company size simultaneously or simultaneously only have la small influence on firm value. Thel results lof this analysisl are input for companies, especially in the banking industry, to apply GCG principles and sustainability reports to increase company value and become attractive to investors